The brave little tailor - McKie, Anne; McKie, Ken (Loughborough : Ladybird Books, 1983)
A tailor who kills seven flies with one blow outwits the king and earns half his kingdom and his daughter's hand in marriage.
Keywords: Children's stories; Fairy tales